Routing for multimedia traffic in wireless frequency-hop communication networks. - Pursley, M.B.
A new method is described for routing multimedia traffic in a frequency-hop (FH) store-and-forward packet radio network. The method is illustrated for traffic of two types, each type having its own throughput, delay, and error-rate requirements. A typical application is the routing of voice and data packets in a distributed multiple-hop network. In such an application, voice packets cannot tolerate much delay, but they are allowed to contain a small number of frame erasures while data packets must be delivered error-free even if a moderate delay is required to do so. The fully distributed routing protocol presented in the paper takes into account the type of service required for each type of traffic, and it adapts to the interference as seen by the FH radio receivers in the network. Our approach to multimedia routing is based on least-resistance routing with different link and path resistance metrics for different message types. Each of the resistance metrics for a link reflects the ability of the link to provide the service required by the one of the message types. This includes, but is not limited to, a measure of the likelihood of successful reception by the FH radio receiver for that link. The route selection for a particular type of packet depends on the resistances of the links along the routes from that packet's source to its destination. In general, different routes may be selected for different types of packets. The primary conclusion of this paper is that the quality of service increases for each of the two types of multimedia traffic if the routing protocol accounts for the type of message that is being relayed
Keywords: FH radio receivers; Data packets; Delay; Distributed multiple-hop network; Distributed routing protocol; Error-rate.; Frame erasures; Interference; Least-resistance routing; Link resistance metric; Mobile terminals; Multimedia traffic routing; Path resistance metric; Quality of service; Routing protocol; Spread-spectrum radio networks; Store-and-forward packet radio network; Throughput; Voice packets; Wireless frequency-hop communication networks